Experimental investigation and thermodynamic modeling of the Zr-Y system - Bu M.J.; Wang P.S.; Xu H.H.; Liu S.H.; Sha C.S.; Du Y.; Pan F.S.; Tang A.T. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Based on the critical review of all the available experimental data in the literature, 8 key alloys were prepared by arc melting to investigate the phase equilibria in the Zr-Y system, These alloys, which were annealed at 5 different temperatures (800°C, 1000°C, 1100°C, 1120°C, 1160°C), were analyzed by means of X-ray diffraction, differential scanning calorimetry, optical microscopy and scanning electron microscopy with energy-dispersive X-ray spectroscopy. The results showed that a peritectoid reaction (βZr) + (αY) = (αZr) occurs at 886°C ± 5°C, and an eutectic reaction L = (βZr) + (αY) occurs at 1313°C ± 5°C. Taking into account the experimental data obtained both from this work and the literature, the Zr-Y system was thermodynamically modeled. The previously reported temperature for the peritectic reaction of (βY) + L = (αY) at about 1490 °C is supported by our thermodynamic calculation. Comparison between the calculated and measured phase diagrams shows that the thermodynamic calculation can well account for the experimental data.